2013
DOI: 10.1111/tme.12020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of buffy‐coat derived platelet components suspended in SSP+ treated with the INTERCEPT Blood system

Abstract: The observed increase in platelet glycolysis following INTERCEPT treatment is consistent with previous literature reports. Importantly, the in vitro changes were less marked than previously reported indicating that the platelets suspended in SSP+ with reduced plasma carryover are of suitable in vitro quality following INTERCEPT treatment and storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 48 publications
7
58
3
Order By: Relevance
“…Treatment with the UVC system appears to accelerate the metabolic rate of platelets, which is similar to the effects of other PI methods [9,10,11]. However, in vivo investigations using the UVC system are showing positive results [5,12].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Treatment with the UVC system appears to accelerate the metabolic rate of platelets, which is similar to the effects of other PI methods [9,10,11]. However, in vivo investigations using the UVC system are showing positive results [5,12].…”
Section: Introductionmentioning
confidence: 77%
“…Extracellular lactate dehydrogenase (LDH) was measured from supernatants using an in vitro toxicology assay (Sigma Aldrich, St. Louis, MO, USA), against a standard curve of L-lactic dehydrogenase. Adenosine triphosphate (ATP) concentration was measured using an ATP bioluminescence kit (Roche, Mannheim, Germany), as previously described [9]. Samples for glucose, LDH, and ATP were tested in triplicate against a standard curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole blood units (450 ± 45 ml) were collected (day 0) into bottom-and-top bags containing 63 ml citrate phosphate dextrose (Fresenius Kabi, Bad Homburg, Germany) and stored at 22 °C between collection and processing. Buffy coat-derived platelets were prepared from four ABO/RhD compatible units with 300 ml SSP+ (MacoPharma, Mouvaux, France), as previously described [27]. The platelet concentrates had a final composition of approximately 70% SSP+ and 30% plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Undoubtedly the storage medium influences platelet response as reported by several studies, 5,6 yet it might indeed have longer-lasting effects which are not reversible, especially after longer storage time (i.e., 3-4 days). In our study, platelets were resuspended in the same storage medium for all treatment groups (untreated and IBS-treated with or without pre-treatment with inhibitors) so the difference between untreated and Amotosalen treated platelets cannot solely be explained by a negative impact of the storage medium nor by the pH, which, even though significantly lower for the Amotosalen/UVA samples (as reported in other studies too 7,8 ), was nevertheless in an acceptable range observed by others and above 7. Besides, for the in vivo analysis of platelet survival in mice, human platelets were washed and resuspended in sterile PBS before i.v.…”
mentioning
confidence: 69%